2006
DOI: 10.1111/j.1365-3164.2006.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermal microdialysis in the dog: in vivo assessment of the effect of cyclosporin A on cutaneous histamine and prostaglandin D2 release

Abstract: Dermal microdialysis, a relatively noninvasive technique, allows investigation of the changes in cellular mediators released during cutaneous allergic responses. This technique was used to evaluate the effect of cyclosporin A, an immunosuppressive drug used for treatment of canine atopic dermatitis, on the cutaneous release of two pro-inflammatory mediators following intradermal allergen challenge. Four beagle dogs spontaneously sensitized to Ascaris suum were treated for 1 month with oral cyclosporin A. At da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Histamine release as well as prostaglandin synthesis have been investigated following mast cell activation in guinea pigs (29), rats (30,31), and dogs (18). following allergenic provocation in guinea pig skin, through the subcutaneous injection of compound 48/80 as well as the intravenous administration of ovalbumin (32), histamine levels increased significantly.…”
Section: Immediate Hypersensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Histamine release as well as prostaglandin synthesis have been investigated following mast cell activation in guinea pigs (29), rats (30,31), and dogs (18). following allergenic provocation in guinea pig skin, through the subcutaneous injection of compound 48/80 as well as the intravenous administration of ovalbumin (32), histamine levels increased significantly.…”
Section: Immediate Hypersensitivitymentioning
confidence: 99%
“…following allergenic provocation in guinea pig skin, through the subcutaneous injection of compound 48/80 as well as the intravenous administration of ovalbumin (32), histamine levels increased significantly. The effect of cyclosporin A on the allergen-induced release of histamine and prostaglandin D2 (PgD2) synthesis has been investigated in dogs (18). Whereas orally administered cyclosporine gradually reduced the allergen-induced histamine release and wheal formation over 30 days of treatment, the rate of PgD2 synthesis surprisingly remained unchanged.…”
Section: Immediate Hypersensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In Shinkai et al [96] another study had proven that the transdermal ketoprofen significantly reduced the PGE-2 skin content and the joint fluid. Brazis et al [97] studied the impact cyclosporin A on the Beagle dogs skin histamine and PGE-2 levels, the results showed that histamine levels were significantly decreased after treatment 15~30 days, but the PGE-2 levels did not change significantly, indicating that cyclosporine inhibiting the release of anti-inflammatory effects of histamine. Study the physiological mechanisms of skin diseases is also a major application areas DMD.…”
Section: The Pharmacodynamics and Mechanism Studymentioning
confidence: 99%
“…Radioenzyme or spectrophotometric enzyme immunoassays [20][21][22][23] , high-performance liquid chromatography (HPLC) [24,25] and spectrofluorometric assays [26] have been used for analysis of histamine in animal and human skin microdialysis samples. However, these methods do not provide the sensitivity and selectivity required for the determination of trace levels of extracellular histamine, and/or they are too laborious or unsuitable for routine use in a standard analytical laboratory.…”
Section: Determination Of Histamine In Microdialysismentioning
confidence: 99%